2018
DOI: 10.3928/1081597x-20180814-02
|View full text |Cite
|
Sign up to set email alerts
|

Effect of NSAIDs on Pupil Diameter and Expression of Aqueous Humor Cytokines in FLACS Versus Conventional Phacoemulsification

Abstract: PURPOSE: To compare the concentrations of interleukin (IL) (IL-1b, IL-2, IL-4, IL-5, IL-6, IL-8, IL-10, IL-12p70), interferon (IFN)-γ, tumor necrosis factor (TNF)-α, and TNF-β in the aqueous humor of patients undergoing femtosecond laser–assisted cataract surgery (FLACS) and corneal mechanical paracentesis treated with two different topical nonsteroidal anti-inflammatory drugs (NSAIDs): bromfenac and indomethacin. METHODS: In this prospective, randomize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 28 publications
1
21
0
Order By: Relevance
“…In a recent study, Liu et al found the lower aqueous malondialdehyde but higher prostaglandin E 2 and interleukin-1 receptor in the FLACS group compared with the conventional group ( 27 ). Also, evaluated interleukin-6 level was found in the FLACS group compared to controls ( 28 ). Nomura et al demonstrated that higher concentrations of CXCL13 were correlated with thicker subfoveal choroidal thicknesses in 76 eyes of cataract patients ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Liu et al found the lower aqueous malondialdehyde but higher prostaglandin E 2 and interleukin-1 receptor in the FLACS group compared with the conventional group ( 27 ). Also, evaluated interleukin-6 level was found in the FLACS group compared to controls ( 28 ). Nomura et al demonstrated that higher concentrations of CXCL13 were correlated with thicker subfoveal choroidal thicknesses in 76 eyes of cataract patients ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is no standard definition in the literature for what constitutes a small pupil. Most commonly pupil diameter less than 5 mm is considered as small[ 22 27 28 ]; however, there is a study that considered pupil diameter of 4 mm or less as small pupil. [ 6 ]…”
Section: Discussionmentioning
confidence: 99%
“…In order to prevent intraoperative difficulties associated with a small pupil, non-steroidal anti-inflammatory drugs should be applied three to four times on the day prior to surgery, and in the morning before surgery. 70,73,74 In a study by Anisimova et al., 70 bromfenac 0.9% prevented the incidence of miosis better than indomethacin 0.1%. Walter et al.…”
Section: An Overview Of Intraoperative Benefits and Drawbacks Of Flacsmentioning
confidence: 97%
“…6769 Moreover, the magnitude of miosis is correlated with the concentration of intracameral interleukin-6. 70 Risk factors for intraoperative miosis during FLACS include longer laser pretreatment duration and older patient age. 71 Also other factors such as short pupil-capsulotomy distance, shallow anterior chamber, smaller pre-operative pupil size, and longer suction time are associated with intraoperative miosis.…”
Section: An Overview Of Intraoperative Benefits and Drawbacks Of Flacsmentioning
confidence: 99%